Microwave plasma atomic emission spectroscopy (MP-AES)—A useful tool for the determination of silicon contents in plant samples? - Puppe, Daniel; Buhtz, Christian; Kaczorek, Danuta; Schaller, Jörg; Stein, Mathias (Frontiers in Environmental Science, 2024)
The accurate quantification of silicon (Si) contents in plant materials represents a fundamental prerequisite for agricultural plant-soil system or terrestrial ecosystem studies. Si contents in plants are usually calculated from Si concentrations determined spectroscopically in corresponding plant extracts. Inductively coupled plasma optical emission spectrometry (ICP-OES) is widely used in environmental sciences for Si measurements, because this technique is characterized by relatively high sensitivity and low expenditure of human labor. However, as an ICP-OES instrument is also characterized by relatively high acquisition and running costs, it is not readily available to most laboratories. Microwave plasma atomic emission spectroscopy (MP-AES) might represent a costeffective alternative to ICP-OES. In our study we compared the results obtained from ICP-OES and MP-AES measurements of Si concentrations in Tiron extracts of husk and straw samples of winter wheat (Triticum aestivum) to evaluate the capability of the MP-AES technique for the determination of Si contents in plant materials. Moreover, we correlated these results with data on plant available Si concentrations in corresponding soil samples as well as phytolith contents in the husk and straw samples to evaluate the performance of MP-AES in biogeochemical Si plant-soil studies. Based on our results we found MP-AES to represent a suitable technique for the reliable determination of Si concentrations in Tiron extracts with negligible matrix effects. Our results clearly indicate that MP-AES represents a promising alternative for all researchers with a focus on biogeochemical Si cycling in general.